Pengaruh Manajemen Keuangan terhadap Kualitas Pendidikan di Lembaga Pendidikan Islam: Studi Kepustakaan - Istikomah, Yayuk; Minarti, Sri (Philosophiamundi, 2025)
This study aims to describe the influence of financial management on the quality of education in Islamic educational institutions using a library research approach. The focus of the study includes five main aspects: effectiveness of financial operations, the link between financial stability and teacher professionalism, the role of transparency and accountability, the impact of financial planning on access to education, and the application of Islamic financial principles. The findings indicate that all these aspects are interrelated and significantly influence the quality of Islamic education services. The study recommends that Islamic educational institutions develop financial management systems that align with Sharia principles and are oriented toward justice, efficiency, and educational sustainability